Dictyostelium discoideum as a Model to Assess Genome Stability Through DNA Repair - Pears, Catherine J.; Brustel, Julien; Lakin, Nicholas D. (Frontiers in Cell and Developmental Biology, 2021)
Preserving genome integrity through repair of DNA damage is critical for human health and defects in these pathways lead to a variety of pathologies, most notably cancer. The social amoeba Dictyostelium discoideum is remarkably resistant to DNA damaging agents and genome analysis reveals it contains orthologues of several DNA repair pathway components otherwise limited to vertebrates. These include the Fanconi Anaemia DNA inter-strand crosslink and DNA strand break repair pathways. Loss of function of these not only results in malignancy, but also neurodegeneration, immune-deficiencies and congenital abnormalities. Additionally, D. discoideum displays remarkable conservations of DNA repair factors that are targets in cancer and other therapies, including poly(ADP-ribose) polymerases (PARPs) that are targeted to treat breast and ovarian cancers. This, taken together with the genetic tractability of D. discoideum, make it an attractive model to assess the mechanistic basis of DNA repair to provide novel insights into how these pathways can be targeted to treat a variety of pathologies. Here we describe progress in understanding the mechanisms of DNA repair in D. discoideum, and how these impact on genome stability with implications for understanding development of malignancy.